2008
DOI: 10.1177/0091270008319330
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aliskiren, a Direct Renin Inhibitor, on Cardiac Repolarization and Conduction in Healthy Subjects

Abstract: This multicenter, double-blind study evaluated the effects of aliskiren, a direct renin inhibitor approved for hypertension, on cardiac repolarization and conduction. Healthy volunteers (n = 298) were randomized to aliskiren 300 mg, aliskiren 1200 mg, moxifloxacin 400 mg (positive control), or placebo once daily for 7 days. Digitized electrocardiograms were obtained at baseline and day 7 of treatment over 23 hours postdose. Placebo-adjusted mean changes from baseline in QTcF (Fridericia corrected), QTcI (indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In the other two studies however, no such effect was found [39],[40]. In these two studies the percentage adverse events was higher compared to the first study [37].…”
Section: Resultsmentioning
confidence: 54%
See 4 more Smart Citations
“…In the other two studies however, no such effect was found [39],[40]. In these two studies the percentage adverse events was higher compared to the first study [37].…”
Section: Resultsmentioning
confidence: 54%
“…In one of the three placebo-controlled studies the data suggest that mild gastrointestinal adverse events occur twice as often after use of moxifloxacin compared to placebo (RR 2.03, 95% CI 1.13–3.64) [37]. In the other two studies however, no such effect was found [39],[40].…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations